The Mamdani fuzzy inference algorithm - Khan, Imran Moez; Htike@Muhammad Yusof, Zaw Zaw; Khalifa, Othman Omran; Lai, Weng Kin (IIUM Press, 2011)
Fuzzy logic is simply the operations of fuzzification, conjunction, disjunction, complement,defuzzification etc. on fuzzy sets. It is generally carried out using the degree of membership that has been discussed so far. The fuzzification step is usually performed on data being input into a system. In the Mamdani fuzzy inference methodology this fuzzified input data to trigger a number of weighted IF-THEN rules that govern the system's behaviour. The firing strength of these rules is determined by separate steps that can also be optimized for design. After individual firing strengths are computed, they are then fed into the system function and the final system output is determined by a defuzzification step.